Determinantes do tráfico de animais silvestres no estado de Goiás e no bioma cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The removal of wild animals in their natural habitat cause a lot of damage to wildlife and to the environment in general. However, the wild animal trafficking is not only related to environmental problems, but also economic and social. Thus, the aim of this work to diagnose the trafficking of wild animals in the states that make up the Cerrado between the years 2006-2013 in order to determine the major ecological, economic and social characteristics governing trade in this biome. To this end, letters were sent to the Battalion of the Environmental Military Police, the Superintendent of the Brazilian Institute of Environment and Renewable Natural Resources and Ministry of the Environment, located in the states that make up the Cerrado Biome, requesting the release of the Terms of Seizure and deposit the relevant information concerning the trafficking of wild animals. The trafficking of wild animals in the states that make up the Cerrado biome is characterized by catching various species within basically five classes, Aves, Reptilia, Mammalia, Amphibia and Pisces. The class that had the highest number of seizures between the years studied was the bird, highlighting the canary-the-earth-true kind (Sicalis flaveola), which was the species most commonly seized in the whole study. With respect to the degree of threat to which the species are seized inserted Note that the category "less concern" we had was the most representative. It observed the existence of spatial gaps in oversight to the state Goiás, which concentrates most of seizures in towns located near the headquarters of regulatory agencies. The Municipal Human Development Index and the municipal population density exerted influence on the number of seizures in Goiás. However, when considering the same variables at state level is noticed that there is no relationship between the number of seizures and the Index Human development and population density. With regard to the Gini index, in neither case was no relationship between the concentration of income and the number of confiscated specimens. In addition, the amount by which individuals are marketed not influence the number of seizures. The birds are trafficked, in general, in order to be kept as pets, especially due to its lush corner. The fact that the animals seized, in most cases, are not endangered demonstrates that commercialization of endangered species is, for the Brazilian Cerrado, a casual event, while the non-threatened species is an expected event. The differences observed for the results of the Human Development Index and population density are due to the fact that in Goiás were evaluated municipal variables, while in other states the evaluation took place on the variables of the state itself. The absence of a relationship between sales value and number of seizures shows that it is more feasible and probably more profitable for traffickers to market animals whose capture easier, thanks to its greater availability in nature, those whose abundance is reduced.
Keywords: Comércio ilegal de animais silvestres; Tráfico de espécies; Conservação; Fiscalização; Comercialização de espécies; legal wildlife trade; Trafficking in species; Conservation; Surveillance; Marketing species; CIENCIAS BIOLOGICAS